Memberdayakan kembali ‘Kesenian Totua’: Revitalisasi Adat Masyarakat To Lindu di Sulawesi Tengah - Gregory L. Acciaioli (Antropologi Indonesia, 2001)
During the new order era local adat was subjected to a process of cultural erosion due to the priorities accorded national integrations, as well as economic, social and development by the Indonesian government. However, the '90s have witnessed a resurgence of concern with adat as a vehicle for the local peoples' identity and as a mechanism for local government and dispute resolution, trends intensified since the beginning of the reformasi era with its relegitimation of discourse of regional autonomy. This essay presents a case study of these processes among Lindu people of Central Sulawesi, focusing upon how they have managed to reinvigorate their adat as a response to two forms of governmental imposition: 1) the encompassment of their land within a national park (i.e. Taman National Lore Lindu); and 2) the plan to construct a hydroelectric project, which would have forced the loss of land to rising water level and resettlement of the local population. The Lindu people have sought there empowerment of their adat by recasting it as a community resource management system that they argue can lead to greater sustainability of local natural resource than any imposed regimen of national park regulations. With assistance of NGOs such as Yayasan Tanah Merdeka, they have also adopted the discourse of 'indigenous people' to defend their continuing right of inhabitation in their homeland in the face of threatened resettlement. This essay explores the cultural politics of masyarakat adat as 'indigenous people' and the invocation of ecologically sound 'indigenous wisdom' as a warrant for resistance to development programs.